2018
DOI: 10.1007/978-3-662-56537-7_85
|View full text |Cite
|
Sign up to set email alerts
|

Motion Artifact Detection in Confocal Laser Endomicroscopy Images

Abstract: Confocal Laser Endomicroscopy (CLE), an optical imaging technique allowing non-invasive examination of the mucosa on a (sub)cellular level, has proven to be a valuable diagnostic tool in gastroenterology and shows promising results in various anatomical regions including the oral cavity. Recently, the feasibility of automatic carcinoma detection for CLE images of sufficient quality was shown. However, in real world data sets a high amount of CLE images is corrupted by artifacts. Amongst the most prevalent arti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Although these motion artefacts are relatively easy for a human examiner to overlook, they represent a relevant interfering factor in automatic analysis. Detection of motion artefacts demonstrated that the performance can be improved by pattern recognition algorithms that recognise malignant changes 34 . For comparison, the results presented in this study gained by two trained and certified examiners show an accuracy of 91.38-96.55%.…”
Section: Discussionmentioning
confidence: 99%
“…Although these motion artefacts are relatively easy for a human examiner to overlook, they represent a relevant interfering factor in automatic analysis. Detection of motion artefacts demonstrated that the performance can be improved by pattern recognition algorithms that recognise malignant changes 34 . For comparison, the results presented in this study gained by two trained and certified examiners show an accuracy of 91.38-96.55%.…”
Section: Discussionmentioning
confidence: 99%
“…Electronics 2024, 13, 724 2 of 13 Researchers have carried out a lot of valuable work to automatically assess CT image quality [4][5][6][7][8][9]. Several studies have mainly focused on handcrafted feature designation.…”
Section: Introductionmentioning
confidence: 99%
“…For medical image quality assess and artifacts detection [ 26 , 27 , 28 ], there are still three major challenges remaining.…”
Section: Introductionmentioning
confidence: 99%